Estudios y diseño definitivo del sistema de alcantarillado sanitario, y pluvial del sitio San José de la parroquia Bellavista del cantón Santa Rosa, provincia de El Oro. - Soto Jaramillo, Gabriela Rosmeri (2015)
Decentralized Autonomous Municipal Government of Santa Rosa Canton order to improve the quality of life of its inhabitants and considering the lack of basic services in some places, which is why with the help of the University Machala technique titling this project develops "ULTIMATE DESIGN STUDIES AND SANITARY SEWER SYSTEM, AND SITE PLUVIAL SAN JOSE PARISH OF CANTON BELLAVISTA SANTA ROSA, PROVINCE OF GOLD." For the effect of it it has been receptado the necessary information such as plans, reports, technical reports and regulations, in order to obtain as a result an optimal and suitable solution that meets the conditions required by the Site Sn Jose Parish Bellavista. to an irrigation canal.